Material practices for meaningful engagement: An analysis of participatory learning and action research techniques for data generation and analysis in a health research partnership. (25th August 2017) - O'Reilly‐de Brún, Mary; de Brún, Tomas; O'Donnell, Catherine A.; Papadakaki, Maria; Saridaki, Aristoula; Lionis, Christos; Burns, Nicola; Dowrick, Chris; Gravenhorst, Katja; Spiegel, Wolfgang; Van Weel, Chris; Van Weel‐Baumgarten, Evelyn; et al.
Abstract: Background: The material practices which researchers use in research partnerships may enable or constrain the nature of engagement with stakeholder groups. Participatory learning and action (PLA) research approaches show promise, but there has been no detailed analysis of stakeholders' and researchers' experiences of PLA techniques for data generation and co‐analysis. Objectives: To explore stakeholders' and researchers' experiences of PLA techniques for data generation and co‐analysis. Design: The EU RESTORE implementation science project employed a participatory approach to investigate and support the implementation of guidelines and training initiatives (GTIs) to enhance communication in cross‐cultural primary care consultations. We developed a purposeful sample of 78 stakeholders (migrants, general practice staff, community interpreters, service providers, service planners) from primary care settings in Austria, England, Greece, Ireland and The Netherlands. We used speed evaluations and participatory evaluations to explore their experiences of two PLA techniques—Commentary Charts and Direct Ranking—which were intended to generate data for co‐analysis by stakeholders about the GTIs under analysis. We evaluated 16 RESTORE researchers' experiences using interviews. We conducted thematic and content analysis of all evaluation data. Results: PLA Commentary Charts and Direct Ranking techniques, with their visual, verbal and tangible nature and inherent analytical capabilities, were found to be powerful tools for involving stakeholders in a collaborative analysis of GTIs. Stakeholders had few negative experiences and numerous multifaceted positive experiences of meaningful engagement, which resonated with researchers' accounts. Conclusion: PLA techniques and approaches are valuable as material practices in health research partnerships.